Natural Resources, Growth and Spatially-Based Development : A View of the Literature - Nelson, B. (Washington, DC: World Bank, 2012)
This paper reviews natural resource "curse", economic growth and related spatial issues literature. Empirical work has established the presence of a negative relationship between growth and natural resource richness. Economic theory suggests a range of explanations: 1) resource booms may induce exchange rate appreciation which squeezes growth enhancing sectors; 2) resource rich economies may be subject to price volatility and trade shocks, both ofr which are destabilizing; 3) natural capital appears to crowd out human capital and may foster inequality; 4) natural resource sectors can feature a weak configuration of linkages, limiting the extent of positive feedback to the rest of the economy; and 5) poor policymaking contributes to their under-performance. Policy prescriptions are relatively clear with respect to the short run macroeconomic handling of resource rents. With regard to institutional dimensions, checks and balances on government activity appear to have high returns in resource rich countries. Spatially based and cluster initiatives may help foster productive linkages, technological upgrading, quality certification and market access.